2001
DOI: 10.1006/dbio.2001.0438
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Sry Is Expressed in Pre-Sertoli Cells and Sertoli and Granulosa Cells Have a Common Precursor

Abstract: The expression of Sry in the undifferentiated, bipotential genital ridges of mammalian XY fetuses initiates testis development and is hypothesized to do so by directing supporting cell precursors to develop as Sertoli cells and not as granulosa cells. To directly test this hypothesis, transgenic mice expressing EGFP under the control of the Sry promoter were produced. After establishing that the transgene was expressed in fetal gonads similarly to endogenous Sry, the spatial and temporal expression of the Sry-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
291
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(311 citation statements)
references
References 34 publications
12
291
0
Order By: Relevance
“…In rainbow trout, these cells are clearly in a different location from those expressing sox9a2 and amh, which are expressed in the vicinity of germ cells both in female and male gonads. In the mouse, granulosa and Sertoli cells are considered to develop from a common precursor (Albrecht and Eicher, 2001) and Amh and Sox9 are classic markers of Sertoli cells. In trout, the localization of amh and sox9a2 expression suggests that these genes are also expressed in granulosa cell precursors, and then cyp19a1 would be expressed in another somatic cell type.…”
Section: Figmentioning
confidence: 99%
“…In rainbow trout, these cells are clearly in a different location from those expressing sox9a2 and amh, which are expressed in the vicinity of germ cells both in female and male gonads. In the mouse, granulosa and Sertoli cells are considered to develop from a common precursor (Albrecht and Eicher, 2001) and Amh and Sox9 are classic markers of Sertoli cells. In trout, the localization of amh and sox9a2 expression suggests that these genes are also expressed in granulosa cell precursors, and then cyp19a1 would be expressed in another somatic cell type.…”
Section: Figmentioning
confidence: 99%
“…SRY is expressed in XY genital ridges between approximately E10.5 and E13 with peak RNA expression at E11.5, al- though little information is available on protein levels. Recent studies showed that SRY was expressed in the central region of genital ridges and then became localized nearer to the gonadal surface and cranial and caudal poles (Albrecht and Eicher, 2001;Bullejos and Koopman, 2001). A cell-tracing experiment using Sry-EGFP transgenic mice demonstrated that SRY-positive cells were closely associated with and sometimes partially surrounded each germ cell at E11.…”
Section: Expression Of Dmy Before and During Testicular Differentiationmentioning
confidence: 99%
“…Recent detailed cell-tracing experiment using Sry-EGFP transgenic mice demonstrated that Sry was expressed in pre-Sertoli cells (Albrecht and Eicher, 2001). In medaka, PGCs are surrounded by the somatic cells derived from lateral plate mesoderm during PGC migration and contribute to gonadal formation (Hamaguchi, 1982;this study).…”
Section: Dmy Positive Cells Are Pre-sertoli Cellsmentioning
confidence: 99%
“…In mammals, Sertoli cell precursors express the male sex-determining gene Sry, which appears to act through this cell type to divert the gonad from the ovarian to the testis pathway (Burgoyne and Palmer, 1993;Albrecht and Eicher, 2001). In mice, one of the first differences between the sexes is an increase in proliferation of Sertoli cells (Schmahl et al, 2000).…”
Section: Proliferation Of Sertoli Precursors May Have a Role In Vertementioning
confidence: 99%
“…Sertoli cells have critical roles in early testis development. Not only are they support cells for germ cells and essential components of testis cords, but there is also evidence that Sertoli cells express Sry and direct the morphogenesis of the entire testis (Burgoyne and Palmer, 1993;Albrecht and Eicher, 2001). In alligators, an early proliferation in Sertoli cell precursors is one of the first morphological differences between the sexes (Smith and Joss, 1994), indicating that proliferation in this critical cell type may be a conserved mechanism in vertebrate testis organogenesis.…”
Section: Introductionmentioning
confidence: 99%